Production and characterization of biosurfactant by isolated Pseudomonas aeruginosa RS6 strain - Nordin, Nordiyana (2016)
Biosurfactants are becoming important alternative to chemical surfactants in almost every sector in the modern industry because of their improved properties compared to their chemical counterparts. Rhamnolipid is among the best known glycolipid type biosurfactants with effective surface properties and high productivity. This study aims to isolate and characterize isolated bacterial strain from different environment conditions with the capacity to produce rhamnolipid-biosurfactants when grown on blue agar plate (BAP) selective medium. Four strains with high activity on BAP selective medium which suggested its potential as good rhamnolipid producer were screened out using combination of modified drop-collapse test, oil spreading and emulsification index (E24) test. A strain with an outstanding performance and demonstrated good activity in all the above mentioned screening methods were successfully isolated and showed comparable results against control samples such as Triton-X 100 and sodium n-dodecyl sulfate (SDS), the chemical surfactants. Using morphological, Gram staining, Biolog Gen III MicroPlate analysis and 16s rRNA sequence analysis, the strain was identified as Pseudomonas aeruginosa and it was designed as the RS6 strain. P. aeruginosa RS6 produced rhamnolipid optimally at pH 7.0 when supplemented with 2.5% (v/v) palm oil (10.17 g/L) and palm olein (8.65 g/L). It reduced the surface tension ranging from 26 to 28 mN/m and showed emulsifying capability up to 62.0%. High performance liquid chromatography (HPLC) and fourier transform infrared spectroscopy (FT-IR) confirmed that biosurfactants produced by this strain was rhamnolipid in nature. In this study, an efficient and simple protocol to screen out rhamnolipid-biosurfactant producing bacteria was used and this finding will also help to add novel members to the biosurfactants group and expanded current knowledge regarding the diversity and productive capability biosurfactants from a single specific strain. Therefore, the biosurfactants produced by this strain might be useful as an alternative to chemical surfactants for a wide range of potential applications.